ACCEPTANCE ANALYSIS OF TECHNOLOGY-BASED PERSONNEL MANAGEMENT INFORMATION SYSTEMS (SIMPATIK) IN SUPPORTING THE IMPLEMENTATION OF E-GOVERNMENT IN THE SEMARANG CITY MANPOWER SERVICE (Journal of Advances in Information Systems and Technology, 2021)
In this digital era, information technology has an important role for institutions, companies, communities, and governments. In carrying out the main tasks of the Semarang City Manpower Service, one of them is evaluating employee performance. In assessing the performance of the Semarang City Manpower Service employees using SIMPATIK which was developed by the Semarang City BKPP which was launched in 2018. Where the implementation of the new system needs to be evaluated further. This is due to the failure to implement e-government services, not because of the quality and capacity of the system, but because of the low user acceptance of these services. Thus, it is necessary to analyse the level of acceptance in using SIMPATIK services at the Semarang City Manpower Service whether it can be evaluated further. So that SIMPATIK can still exist to be used for various kinds of services contained in the application by ASN at the Semarang City Manpower Service. The method applied to data collection is the interview and questionnaire method. While the method applied to evaluate SIMPATIK is the Technology Acceptance Model (TAM) by applying four research variables, namely perceived usefulness (PU), perceived ease of use (PEOU), attitude toward using (ATU), and behavioural intentions (BI). To examine the data adopted the method of Structural Equation Model-partial Least Square (SEMPLS). The conclusion reached in this study is that all hypotheses developed in this study were accepted, except for PU on BI rejected because the value of T-Statistics (0.846) < T-Table (1.96) and P-Values were more than 0.05 with a value of 0.398 .